Effect of Addition of Cetylpyridinium Chloride Cationic Surfactant on the Antimicrobial Activity of Chlorhexidine Endodontic Irrigant - Hiba A. Al-Sada; Hikmet A. Al-Gharrawi (Hindawi Limited, 2024)
Background. Endodontic irrigants are essential for disinfecting the root canal system. None of the currently available irrigants perfume sufficiently. However, most products contain surfactants, which enhance the antimicrobial properties of the irrigants. Objectives. To evaluate the effect of cetylpyridinium chloride (CPC) surfactant on the antimicrobial activity of chlorhexidine and compare it with that of chlorhexidine (CHX) and Biopure MTAD against Enterococcus faecalis, Staphylococcus aureus, and Candida albicans. Materials and Methods. In this in vitro study, three microorganisms were used (E. faecalis, S. aureus, and C. albicans), and each organism was treated with three different irrigants: 2% CHX, 2% CHX + 0.2% CPC, and 100% Biopure MTAD. The antimicrobial activity was evaluated by direct contact assay for 5 min of contact time. The colony-forming unit per mL was calculated after antimicrobial treatment and 24 hr of incubation at 37°C. The data were statistically analyzed using Statistical Package for Social Science (SPSS) version 22. The Kruskal-Wallis and the multiple Wilcoxon sum rank tests were used. The level of significance was set at 0.05. Results. The result showed a nonsignificant difference between the different irrigants against E. faecalis. Among S. aureus subgroups, 2% CHX was statistically significant and more efficient than MTAD. Among C. albicans subgroups, 2% CHX and combined irrigant (2% CHX + 0.2% CPC) were statistically more efficient than MTAD. The 2% CHX and combined irrigants were equally effective against all the tested microorganisms. Conclusions. All the used irrigants have comparable effects against E. faecalis after 5 min. CHX have a comparable effects to that of the combined irrigant and more efficient against S. aureus than MTAD. CHX and the combined irrigant have potent antimicrobial activity against C. albicans superior to MTAD. CPC surfactant can be used with CHX to overcome its clinical drawbacks or limitations without altering or reducing its antimicrobial activity.